2022
DOI: 10.1039/d1ta10531k
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh reversible lithium storage of hierarchical porous Co–Mo oxides via graphene encapsulation and hydrothermal S-doping

Abstract: The construction of a complex structure and component adjustment are effective strategies for improving volume expansion and conductivity of transition metal oxides, which serve as promising anode materials in lithium-ion...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…The authors concluded that the oxidative etching reaction initiates and propagates mainly in oxygen-deficient regions, preferentially removing oxygen-containing carbon atoms, generating carbon vacancies, and eventually forming nanopores in the GO nanosheets. A simple metal-organic framework production strategy was proposed by Zhu et al [ 31 ] Layered porous CoMoO 4 -CoO/S@rGO nanopolyhedra were synthesized by hydrothermal S-doping, as shown in Figure 2 b. The preparation process can be divided into two parts; the first step synthesizes dodecahedral-shaped ZIF-67 crystal as the initial precursor.…”
Section: Preparation Of Iva-ldmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that the oxidative etching reaction initiates and propagates mainly in oxygen-deficient regions, preferentially removing oxygen-containing carbon atoms, generating carbon vacancies, and eventually forming nanopores in the GO nanosheets. A simple metal-organic framework production strategy was proposed by Zhu et al [ 31 ] Layered porous CoMoO 4 -CoO/S@rGO nanopolyhedra were synthesized by hydrothermal S-doping, as shown in Figure 2 b. The preparation process can be divided into two parts; the first step synthesizes dodecahedral-shaped ZIF-67 crystal as the initial precursor.…”
Section: Preparation Of Iva-ldmentioning
confidence: 99%
“…Reprinted with permission from Ref. [ 31 ]. Copyright 2022 American Association for the Journal of Materials Chemistry A.…”
Section: Figurementioning
confidence: 99%
“…Compositing with carbon materials has been proved to be an effective method to enhance electrical conductivity, increase structural stability, and relieve volume variation, such as graphene oxide (GO) encapsulation, carbon coating, and carbon fiber. [21][22][23][24][25] Ingenious morphology design is also one of the commonly adopted strategies. 26,27 Novel structural designs, such as porous, hollow, and core-shell structures, provide larger specific surface area and ample volume space, which means that the electrode material offers more lithium storage sites and alleviates volume expansion, thereby acquiring higher specific capacity and enhanced cycle stability.…”
Section: Introductionmentioning
confidence: 99%
“…6 Nevertheless, the slow kinetics and relatively low theoretical capacity (372 mA h g −1 ) of the most common insertion anode material, graphite, are no longer able to meet the growing demand for energy density. 7,8 In addition, the working potential of graphite (<0.1 V vs. Li + /Li) is close to the growth potential of lithium dendrite, which poses serious safety issues. 9,10 Although conversion and alloy type anode materials possess higher theoretical capacity, 11 the severe volume expansion during lithiation and delithiation prevent them from achieving long cycles.…”
Section: Introductionmentioning
confidence: 99%